African American Women’s experiences as teen mothers and their persistence in higher education - Tamara Coats (Adult Education Research Conference, 2016)
The purpose of this pilot study is to explore the African American mother-daughter communicative relationship about teen pregnancy and the effects on one’s college degree attainment. A research study of narratives was used to explore the teen pregnancy experience of three African American adult women who are pursuing graduate degrees.
Keywords: African-American Education Communication